Financial Development in Emerging Europe : The Unfinished Agenda - Zoli, Edda (IMF Working Papers; Working Paper ;, 2007)
This paper assesses the status of financial development in Emerging Europe, analyzes the factors that have shaped it, and discusses policy priorities. Financial development has progressed to varying degrees across the region. Macroeconomic stability and institutional quality have been important factors. Going forward, the EU integration process is likely to propel further reforms and shape financial development in EU members. In non-EU emerging economies the focus should be on maintaining macroeconomic stability and strengthening law enforceability. Creating a well-functioning government securities market, reinforcing corporate governance and creditor rights protection, and promoting the emergence of institutional investors would be beneficial.